(untitled) (Journal of Asian Development Studies, 2024)
The economic vitality or momentum of any economy is contingent upon the success of the industrial sector. The rise in industrial production indicates economic progress, improved livelihoods, enhanced access to necessities and increased domestic investments. Economic strength transforms into economic weakness if the industrial sector is not producing the desired outcome. This study investigates how tax revenue and money supply relate to Singapore’s industrial production in order to understand more about the shifting trends in the country’s industrial output. This study takes into account FDI inflows, domestic listed companies and electric power consumption as controlling factors of industrial production function. The ARDL bounds test has been employed over the period from 1980-2022. The empirical findings provide evidence of cointegrating relation between industrial production and its regressors in the long run. The results further demonstrate that tax revenue as an instrument for fiscal policy and money supply as an instrument for monetary policy are significantly escalating industrial production but between both, money supply has a stronger impact on industrial production. This study suggests that expansionary monetary policy and expansionary fiscal policy may be adopted to accelerate industrial production in Singapore while keeping the cost of conducting these policies in mind. Furthermore, FDI inflows and domestic listed companies are also advised to be encouraged as these give a boost to industrial production.